Beyond the screen: Dissecting the nexus of victimization and cyberhate among adolescents through excessive internet use, online interactions with strangers and parental restrictions. - Korol, Liliia; Blaya, Catherine (British Journal of Psychology, 2025)
Prior research has established that being a target of offline and online victimization might function as a significant risk factor that increases the likelihood of adolescents' involvement in cyberhate. Yet, relatively little is known about the mediating and moderating mechanisms underlying this relationship. To fill this important gap in knowledge, the present study aims to examine (1) whether excessive Internet use and contact with unknown people online act as sequential mediators in the relationship between overall victimization and youth's involvement in cyberhate; and (2) whether restrictive parental mediation has any role to play in moderating this relationship. The findings suggest that adolescents who experience victimization are more likely to turn to using the Internet excessively, and consequently interact with strangers online, which in turn makes them more prone to becoming victim to cyberhate or spreading hateful content online themselves. Moreover, restrictive parental mediation was shown to exacerbate the link between excessive Internet use and adolescents' contacts with unknown people online, thereby putting them at higher risk of cyberhate involvement. The current study emphasizes the need for a balanced approach to parental mediation – one that fosters open communication, trust and the development of digital literacy skills.